The Ray of Light: An Activity Approach of Reggio Emilia - Mahshulah, Zulma Aimmatul; Syaodih, Ernawulan; Rachmawati, Yeni (International Conference on Elementary Education, 2020)
The article entitled The Ray of Light: An Activity Approach of Reggio Emilia is a literature review. This article aims to reveal how light can play a role in early childhood education. Exploration activities using light can stimulate critical thinking skills in children. The use of light in the realm of early childhood education was introduced Loris Malaguzzi who was named reggio emilia approach. The reggio emilia approach uses the Vigotsky theory, Piaget theory and uses the philosophy of John Dewey. This approach gives freedom to children to choose their own learning activities, solve a problem, cooperate with others so that children can build their own critical thinking skills and social abilities. The use of light in early childhood education is known as the ray of light atelier, which is a place for children to conduct research and experiments using light. Children who are given the freedom to experiment with light, can provide opportunities to teach children about the concepts of science, namely reflection, refraction, as well as introducing the concept of size and color